Comparison of reduced and sulfided CoMo/γ‐Al2O3 catalyst on hydroprocessing of pretreated bio‐oil in a continuous packed‐bed reactor. Issue 4 (29th December 2014) - Parapati, Divya R.; Guda, Vamshi K.; Penmetsa, Venkata K.; Tanneru, Sathish K.; Mitchell, Brian; Steele, Philip H.
<x xml:space="preserve">Abstract</x> Pretreated bio‐oil was hydroprocessed with conventional sulfided CoMo/γ‐Al2O3 catalyst in a continuous packed‐bed reactor. Hydroprocessing experiments were performed at a temperature of 350 to 400°C, 1500 psig hydrogen pressure, using a hydrogen flow rate of 500 mL/min at a liquid hourly space velocity of 0.2 h−1. The results from sulfided catalytic experiments were compared with our prior studies on hydroprocessing pretreated bio‐oil with reduced CoMo/γ‐Al2O3 catalyst. sulfided CoMo/γ‐Al2O3 catalyst demonstrated higher catalytic activity and resulted in increased hydrocarbon fraction yields. Moreover, the quality of the hydrocarbon fraction, as determined by the acid value, higher heating value, and water content analysis, also improved. Sulfided CoMo/γ‐Al2O3 catalyst produced a hydrocarbon fraction having a higher heating value of 44.4 MJ/kg, acid value of 0.5 mg KOH/g oil, and a total water content of 0.1%. Use of sulfided catalyst for hydroprocessing pretreated bio‐oil decreased the oxygen content from 47.8 wt % in the pretreated bio‐oil to nondetectable limits (∼0 wt %) in the hydrocarbon fraction. The hydrocarbon fraction was also analyzed by detailed hydrocarbon analysis and simulated distillation. © 2014 American Institute of Chemical Engineers Environ Prog, 34: 1174–1179, 2015